2015
DOI: 10.5194/acp-15-2489-2015
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive laboratory study on the immersion freezing behavior of illite NX particles: a comparison of 17 ice nucleation measurement techniques

Abstract: Abstract. Immersion freezing is the most relevant heterogeneous ice nucleation mechanism through which ice crystals are formed in mixed-phase clouds. In recent years, an increasing number of laboratory experiments utilizing a variety of instruments have examined immersion freezing activity of atmospherically relevant ice-nucleating particles. However, an intercomparison of these laboratory results is a difficult task because investigators have used different ice nucleation (IN) measurement methods to produce t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
328
1
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 221 publications
(364 citation statements)
references
References 95 publications
18
328
1
3
Order By: Relevance
“…Thus, for immersion freezing, we find that the Raman microscope cold stage setup can be used to intercompare inherent immersion freezing abilities of particle types to other instruments under the singular or modified singular approximation. This ability of the Raman microscope cold stage to determine the inherent immersion freezing ability of NX-Illite nanopowder has also been verified (Hiranuma et al, 2015).…”
Section: Validation Of Immersion Freezing Experiments With Kaolinitementioning
confidence: 91%
See 1 more Smart Citation
“…Thus, for immersion freezing, we find that the Raman microscope cold stage setup can be used to intercompare inherent immersion freezing abilities of particle types to other instruments under the singular or modified singular approximation. This ability of the Raman microscope cold stage to determine the inherent immersion freezing ability of NX-Illite nanopowder has also been verified (Hiranuma et al, 2015).…”
Section: Validation Of Immersion Freezing Experiments With Kaolinitementioning
confidence: 91%
“…For each ash, the BET specific surface area was used as determined in this study (Table 1). The modified singular approximation was not used because larger particle-to-particle variability of ice active sites is expected for these complex samples, limiting the importance of time dependence (Broadley et al, 2012;Hiranuma et al, 2015). As shown in Fig.…”
Section: Immersion Freezing Of Droplets Containing Volcanic Ash Samplesmentioning
confidence: 99%
“…Single-particle measurements of T O / T SiO 3 (τ ) vs. the combined potassium and sodium content are shown in the top panel (a). Panel (b) reports the particle number fractions determined by the peak analysis classification method (grey bars), and bulk mass fractions of minerals reported by XRD analysis of illite NX from Hiranuma et al (2015), and IMt-2 and ISCz-1 from Vogt (2002) (red bars). ion formation time, ion trajectory through the ion optics, and temporal jitter of the timing electronics all contribute to differences in arrival times of a certain ion species at the TOF-MS detector.…”
Section: Discussionmentioning
confidence: 99%
“…Sample ISCz-1 is an example of a clay that consists of microscopic interlayers of illite and smectite clay minerals (ISCM). Recently, Broadley et al (2012) suggested illite NX (B+M Nottenkamper, Munich, Germany) as a suitable representation of ambient mineral dust sampled at remote locations and it has been used in numerous ice nucleation studies (Hiranuma et al, 2015). Illite NX is a clay-rich nanopowder that contains significant mineralogical impurities.…”
Section: Dust Samplesmentioning
confidence: 99%
“…The intrinsic heterogeneous ice nucleation abilities of these substances have been characterised in previous AIDA measurement campaigns. The materials include: (i) an Illite NX sample (Arginotec, NX Nanopowder) that was recently distributed as a surrogate for natural desert dusts in a comprehensive laboratory study of ice nucleation measurement techniques (Hiranuma et al, 2015); (ii) a Saharan dust surface sample (SD2) collected about 50 km north of Cairo, Egypt ; (iii) an Israeli dust sample (ID) collected from Ramat Hasharon as sediment soil after a dust storm ; (iv) a Canary Island dust surface sample (CID) collected near the town of Mala on the Island of Lanzarote as a proxy for settled Saharan dust after airborne transport Koehler et al, 2010); (v) a volcanic ash surface sample (EY01) collected 58 km from the Eyjafjallajökull volcano on Iceland 2 days after a major eruption phase in April 2010 (Steinke et al, 2011); and (vi) Graphite Spark Generator (GSG) soot particles from a commercial graphite spark generator (GfG 1000, Palas) (Möhler et al, 2005).…”
Section: Mineral Dust Volcanic Ash and Soot Particlesmentioning
confidence: 99%